Quantitative phosphoproteomics analyses reveal the regulatory mechanisms related to frozen-thawed sperm capacitation and acrosome reaction in yak (Bos grunniens) - Zhang, Renzheng; Liang, Chunnian; Guo, Xian; Bao, Pengjia; Pei, Jie; Wu, Fude; Yin, Mancai; Chu, Min; Yan, Ping (Frontiers in Physiology, 2022)
Mammalian spermatozoa are not mature after ejaculation and must undergo additional functional and structural changes within female reproductive tracts to achieve subsequent fertilization, including both capacitation and acrosome reaction (AR), which are dominated by post-translational modifications (PTMs), especially phosphorylation. However, the mechanism of protein phosphorylation during frozen-thawed sperm capacitation and AR has not been well studied. In this study, the phosphoproteomics approach was employed based on tandem mass tag (TMT) labeling combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) strategy to analyze frozen-thawed sperm in Ashidan yak under three sequential conditions (density gradient centrifugation-based purification, incubation in the capacitation medium and induction of AR processes by the calcium ionophore A23187 treatment). The identification of 1377 proteins with 5509 phosphorylation sites revealed changes in phosphorylation levels of sperm-specific proteins involved in regulation of spermatogenesis, sperm motility, energy metabolism, cilium movement, capacitation and AR. Some phosphorylated proteins, such as AKAP3, AKAP4, SPA17, PDMD11, CABYR, PRKAR1A and PRKAR2A were found to regulate yak sperm capacitation and AR though the cAMP/PKA signaling pathway cascades. Notably, the phosphorylation level of SPA17 at Y156 increased in capacitated sperm, suggesting that it is also a novel functional protein besides AKAPs during sperm capacitation. Furthermore, the results of this study suggested that the phosphorylation of PRKAR1A and PRKAR2A, and the dephosphorylation of CABYR both play key regulatory role in yak sperm AR process. Protein-protein interaction analysis revealed that differentially phosphorylated proteins (AKAP3, AKAP4, FSIP2, PSMD11, CABYR and TPPP2) related to capacitation and AR process played a key role in protein kinase A binding, sperm motility, reproductive process, cytoskeleton and sperm flagella function. Taken together, these data provide not only a solid foundation for further exploring phosphoproteome of sperm in yak, but an efficient way to identify sperm fertility-related marker phosphorylated proteins.